Non-Opioid Otolaryngology Medical Practice - Samba Siva Reddy Bathula; Dustin Jones DO (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Introduction: Opioids have been used as pain medications in the United States since the late 1990s and have become increasingly common since then. Following the declaration of a public health emergency by the US Department of Health and Human Services (US-HHS), the author switched from opioid-based pain management to non-opioid-based pain management without any significant pain concerns from his postoperative patients. The primary purpose of this article was to demonstrate how much opioids in morphine milligram equivalents (MME) was prescribed per month by the author according to Michigan Prescription Monitoring Program (PMP) Prescriber Activity Reports before and after 2018 for management of pain in his otolaryngology postoperative surgical patients. Methods: A retrospective research methodology was employed for this investigation. Michigan PMP Prescriber Reports were collected before and after 2018 and were included in this study. Results: The author prescribed opioid pain medications before the HHS declaration. After the HHS declaration, the author prescribes acetaminophen and Nonsteroidal Anti-Inflammatory Drugs (NSAIDs). The number of opioid prescriptions from the author were remarkably low compared to similar prescribers and others within the author's specialty.  Prescription by MME showed no notable difference in MME values from 0-50 before and after the HHS declaration among the author and SP groups, but a notable drop of MME values from 51-90 among all groups after the HHS declaration. Discussion: The author discourages the use of opioid pain medications for routine otolaryngology procedures. This study demonstrates the effective use of acetaminophen with or without NSAIDs (ibuprofen and diclofenac) to facilitate patient care absent of the well-established dangers of opioid use.